PIJAKAN HUKUM FORMIL PERADILAN AGAMA YANG BERLANDASKAN KAIDAH-KAIDAH FIQHIYAH - Jamil, Jamal (Jurnal Al-Qadau: Peradilan dan Hukum Keluarga Islam, 2014)
To uphold substantive law or procedural law required often called formal law. The procedural law is a provision for setting out how the law (substantive) that materialized or can be applied / implemented to meet the subject deeds. Without judicial procedure there is no substantive legal benefits. To enforce the provisions of criminal law required criminal procedural law, for civil law the existing civil procedural law. The procedural law should be controlled by legal practitioners, police, prosecutors, lawyers and judges. Supremacy of law should start from law enforcement itself. The most important it is to begin from the most high-officials of the supreme court ([MA]) should really implement it strictly legal material. will come to pass new laws that actually among subordinates is necessary to know the rules or Qaeda in proceedings in court, the main event of religious courts.